Quality of Horticultural Crops: A Recurrent/New Challenge for Plant Scientists in a Changing World - Nadia Bertin (Frontiers Research Topics, 2018)
Besides increasing crop yield to feed the growing population, improving crop quality is a challenging and key issue. Indeed, quality determines consumer acceptability and increases the attractivity of fresh and processed products. In this respect, fruit and vegetables, which represent a main source of vitamins and other health compounds, play a major role in human diet. This is the case in developing countries where populations are prone to nutritional deficiencies, but this is also a pending issue worldwide, where the growing middle class is increasingly aware and in search of healthy food. So a future challenge for the global horticultural industry will be to answer the demand for better quality food in a changing environment, where many resources will be limited. This e-collection collates state-of-the-art research on the quality of horticultural crops, covering the underlying physiological processes, the genetic and environmental controls during plant and organ development and the postharvest evolution of quality during storage and processing.